STRATEGI PEMBELAJARAN PENDIDIKAN SEKSUAL UNTUK REMAJA AUTIS DI SMPLB - RETNAWATI, LINDA (Jurnal Pendidikan Khusus, 2017)
Abstract In adolescent phase various changes happened either physic or psychic. The changes happened would make the autism children confused. The autism had hindrance in communication side and social interaction side which caused the changes need some counseling, explaining, and directing so that it required sexual education for autism children. The learning strategy of sexual education was conveyed so that it prevented negative sexual behavior to autism children and supplied them entering their adolescent age. This research used qualitative approach and this research kind was qualitative behaving descriptive. The methods used in collecting data were observation, interview, and documentation while to analyze data used data condensation, data presentation, and taking conclusion. The research result and the data analysis indicated that the learning strategies used were group-individual learning and direct learning. The learning procedure of sexual education in SMPLB Cita Hati Bunda Sidoarjo involved pre instructional step, instructional step, and evaluation / follow-up. Pre instructional steps were deciding the learning purpose by doing assessment activity first, making learning program (individual or classical) in the form of PPI (AP form) or RPP, and preparing media and material needed in learning sexual education. Instructional and follow-up steps involved presenting material (demonstrating knowledge and skill), connecting (correlation, association or guiding training), concluding and giving feedback, and training of concept application. The learning methods of sexual education used in SMPLB Cita Hati Bunda Sidoarjo were demonstration method, drill method, telling story method, simulation method, assignment method, communication method through pictures and videos. The disturbance factors in applying the strategy of learning sexual education in SMPLB Cita Hati Bunda Sidoarjo were the mild and severe hindrance of the students’ behavior, the students’ intelligence level, and less sufficient learning media used.   Keyword :  The learning strategy,  sexual education